KEPEMIMPINAN, KARAKTERISTIK PEKERJAAN, PROSPEK KARIR DALAM MEMOTIVASI KERJA KARYAWAN - Sulaimiah Sulaimiah; Djoko Supyateno (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
This study aims to determine the significant influence of Leadership, Job Characteristics and Career Prospects on the work motivation of sub-section general employees and staffing on the agency's scope of government in East Lombok district. The research method is used with an associative method by using a sample of 51 respondents taken by random sampling with Slovin formula scattered throughout the general sub-division and staffing in the East Lombok district government agencies. Data collection method using questionnaire and documentation method, the type of data used is Primary data taken from respondent and secondary responses. The analytical tool used is multiple regression with F-test and t-test and partial determinant test, validity, reliability, and classic assumption test. While the results show Leadership, Job Characteristics, and Career Prospects have a significant effect on Work Motivation, while leadership, work characteristics, and career prospects have a significant partial effect on work motivation. The dominant test with the partial determinant test seen dominant is the Job Characteristics.